Evaluation of the Lactate Threshold during Downhill Running in Rats - Shimizu, Michele Eisemann; Oki, Sadaaki; Umei, Namiko; Ono, Takeya; Otsuka, Akira; Tsumiyama, Wakako (Journal of Physical Therapy Science, 2014)
[Purpose] The purpose of the present study was to investigate if lactate thresholds in rats could be accurately determined during downhill running in rats. [Subjects] Twenty-four female Wistar rats were used in this study. Rats were randomly divided into two groups: the level running group and downhill running group. [Methods] Catheters were inserted into the right external jugular veins of the rats. Two days after the operation, the rats performed incremental exercise tests. The level running group ran on a treadmill at a 0° incline; the downhill running group ran on a treadmill at a −16° incline. The lactate threshold was determined using the 2-line combination that minimizes the total sum of squares for fitting all data. [Results] Maximal running speeds and running speeds at the lactate threshold for the downhill running group were significantly higher than those for the level running group. [Conclusion] In this study, it was possible to accurately determine the lactate threshold during downhill running. These findings suggest that when the treadmill speed is the same, downhill running can be done at lower metabolic intensity than level running.